2011
DOI: 10.1128/aem.01422-10
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of a Cryptosporidium Isolate from a Southern Elephant Seal ( Mirounga leonina ) from the Antarctic Peninsula

Abstract: The presence ofCryptosporidiumandGiardiain 221 fecal samples from different species of Antarctic pinnipeds was investigated by immunofluorescence microscopy and PCR.Cryptosporidium, a skunk-like genotype, was detected only in a southern elephant seal.Giardiawas not detected. This is the first report of aCryptosporidiumsp. in Antarctic marine mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Molecular research on marine mammals has identified C. muris, seal genotypes 1-4 and a genotype similar to the skunk genotype in seals (Santín et al 2005;Rengifo-Herrera et al 2011;Bass et al 2012;Rengifo-Herrera et al 2013).…”
Section: Cryptosporidium In Birdsmentioning
confidence: 99%
“…Molecular research on marine mammals has identified C. muris, seal genotypes 1-4 and a genotype similar to the skunk genotype in seals (Santín et al 2005;Rengifo-Herrera et al 2011;Bass et al 2012;Rengifo-Herrera et al 2013).…”
Section: Cryptosporidium In Birdsmentioning
confidence: 99%
“…Analysis indicates that subtypes from humans and wildlife are genetically similar and zoonotic transmission might play a potential role in human infections (Guo et al., 2015). The skunk and mink genotypes have also been reported in a few human cases of cryptosporidiosis (Robinson et al., 2008, Chalmers et al., 2009, Rengifo-Herrera et al., 2011, Elwin et al., 2012, Ng-Hublin et al., 2013, Ebner et al., 2015). …”
Section: Wildlife Associated Outbreaks and Water Contaminationmentioning
confidence: 99%
“…Data linking presence in seawater to food-borne illness Very large numbers of cryptosporidial oocysts can occur in the faeces of infected animals (up to 10 9 /g) and inputs into marine environments can occur via freshwater (Fayer et al, 2004) from human sewage and bathers (both C. parvum and C. hominis; (Graczyk et al, 2007), from livestock, domestic and wild animals including rodents (C. parvum). Cryptosporidium has been detected in marine mammals (Hughes-Hanks et al, 2005;Rengifo-Herrera et al, 2010) although their infectiousness to humans is poorly understood, however C.hominis has been detected in a dougon in Australia (Morgan et al, 2000). Outbreaks associated with contaminated drinking water have been reported world-wide (Fayer et al, 2004;LeChevallier and Moser, 1995).…”
Section: Cryptosporidium Giardia and Toxoplasmamentioning
confidence: 99%
“…Cryptosporidium has been detected in marine mammals (Hughes-Hanks et al, 2005;Rengifo-Herrera et al, 2010) although their infectiousness to humans is poorly understood, however C.hominis has been detected in a dougon in Australia (Morgan et al, 2000). Outbreaks associated with contaminated drinking water have been reported world-wide (Fayer et al, 2004;LeChevallier and Moser, 1995).…”
Section: Data Linking Presence In Seawater To Food-borne Illnessmentioning
confidence: 99%